1,2,4,3-Triazaborole-based neutral oxoborane stabilized by a Lewis acid - Loh, Ying Kai (2016)
The first example of 1,2,4,3-triazaborole-based oxoborane has been synthesized via hydrogen migration upon the coordination of AlCl3 to the corresponding borinic acid. X-ray diffraction analysis and computational study disclosed the partial B[double bond, length as m-dash]O double-bond property.